Screening common bean (P. vulgaris L.) germplasm for Fe and Zn biofortication - Caproni, L.; Raggi, L.; Talsma, Elise F.; Santos, Luís Guillermo; Gereda, Javier Mauricio; Londoño Hernandez, Luis Fernando; Wenzl, Peter; Beebe, Stephen E.; Negri, V. (International Center for Tropical Agriculture, 2018)
Among Plant Genetic Resources for Agriculture, landraces are excellent genetic materials for developing new varieties. Due to their genetic diversity, these populations have maintained potentially useful alleles for increasing valuable traits in crops. A diet mostly relying on pulses as source of proteins could not guarantee a proper intake of mineral such as iron (Fe) and zinc (Zn). Indeed Fe and Zn deficiency can lead to serious medical conditions, especially in developing countries. In this context, biofortification is regarded as a sustainable and an effective approach to cope with such a form of malnutrition. Common bean, the most widely used pulse in the world, shows wide diversity regarding Fe and Zn seed content and of anti-nutritional compounds such as phytate (phytic acid, InsP6, and its derivatives, InsP5 and InsP4); the latter reduces absorption of trace-elements including the two above-mentioned minerals. Exploring the natural variability of these compounds in purposely developed collections is the first step towards biofortification of common bean